Modeling the transition from coal to SMRs in Colombia: emissions avoidance under deterministic and probabilistic frameworks - Prieto Valderrama, Camilo; Patiño, Diego (Frontiers in Energy Research, 2025)
The coal-to-nuclear strategy offers a promising pathway for decarbonizing Colombia’s electricity sector while improving system reliability. This study evaluates the potential CO₂-equivalent (CO₂eq) emission reductions resulting from the replacement of coal-fired power plants with small modular reactors (SMRs) over the period 2035 to 2052. Two methodological approaches were used: a deterministic model based on projected installed capacities, decommissioning schedules, and fixed emission factors; and a stochastic Monte Carlo simulation incorporating uncertainty in emission rates and plant performance. The deterministic model estimates a total of 82.62 MtCO₂eq of avoided emissions, while the probabilistic approach yields a median value of 76.04 MtCO₂eq with a standard deviation of 6.58 MtCO₂eq. These consistent results across both methods demonstrate the robustness of the strategy under different technical assumptions. The findings support the viability of coal-to-nuclear replacement as a key contributor to Colombia’s climate goals. In addition to mitigating greenhouse gas emissions, the integration of SMRs could enhance grid resilience by reducing reliance on hydroelectric generation, which is vulnerable to climate variability, and by lowering local air pollution from coal combustion. The analysis underscores the importance of regulatory support and technical planning to enable the deployment of nuclear technologies as part of Colombia’s long-term energy transition.